Novel roles of the multi-functional CCR4-NOT complex in post-transcriptional regulation - Inada, Toshifumi; Makino, Shiho (Frontiers in Genetics, 2014)
The CCR4-NOT complex is highly conserved gene silencer, and more general functions of the complex have been elucidated at post-transcriptional levels. Specific regulatory proteins, including miRNA-induced silencing complex and its associate protein, bind to 3’-UTR elements and recruit the CCR4-NOT complex to promote poly(A) shortening and repress translation and/or degrade the mRNA. Recent studies have revealed that the CCR4-NOT complex tethered by the regulator(s) represses translation and facilitates mRNA decay independent of a poly(A) tail and its shorting. Besides deadeanylase activity, the CCR4-NOT complex has an E3 ubiquitin ligase activity and is involved in a novel protein quality control system, co-translational proteasomal degradation of aberrant protein. In this review, we describe recent progresses on novel roles of the multifunctional complex CCR4-NOT in post-transcriptional regulation.